Laparoscopic Treatment of Presinusoidal Schistosomal Portal Hypertension Associated With Postoperative Endoscopic Treatment: Results of a New Approach. Issue 2 (April 2017) - Colaneri, Renata P.; Coelho, Fabrício F.; de Cleva, Roberto; Herman, Paulo
Abstract : Aim: To propose a laparoscopic treatment for schistosomal portal hypertension. Methods: Ten patients with schistosomiasis and portal hypertension, with previous gastrointestinal hemorrhage from esophageal varices rupture, were evaluated. Patients were subjected to a laparoscopic procedure, with ligature of splenic artery and left gastric vein. Upper gastrointestinal endoscopy was performed on the 30th postoperative day, when esophageal varices diameter was measured and band ligature performed. During follow-up, other endoscopic procedures were performed according to endoscopy findings. Results: There was no operative mortality. One patient had a postoperative splenic infarction that was conservatively treated. Mean hospitalization time was 5 days. During endoscopy 30 days after surgery, a decrease in variceal diameters was observed in 6 patients. During follow-up (mean 84 mo), after endoscopic therapy 8 patients had eradicated varices, but 4 presented with recurrence. Considering the late postoperative evaluation, all patients had a decrease in variceal diameters. A mean of 3.8 endoscopic banding sessions were performed per patient. Two patients presented bleeding recurrence; one had a minor bleeding episode and the other had 2 episodes of bleeding varices requiring blood transfusion. In both patients, bleeding was controlled with endoscopic therapy. No late mortality was observed. Conclusions: Laparoscopic ligature of the splenic artery and the left gastric vein is a promising and less-invasive method for the treatment of schistosomal portal hypertension.